Evaluación de las Propiedades Físico-Mecánicas de Morteros con la Adición de Caucho Molido (2022)
Within the objectives of sustainable development, actions for the environment are established (Naciones Unidas, 2022), this given the problems that the world is currently experiencing, of which the construction industry is one of the most polluting, since generates large amounts of water consumption and contributes to greenhouse gases.